PENGARUH KOMUNIKASI INTERPERSONAL BARISTA TERHADAP KEPUASAN PELANGGAN KAFE TERAS SENJA - Raditya Hutomo (2024)
The phenomenon of high coffee shop business makes the coffee shop business very competitive. Entrepreneurs must be able to create service of excellence in order to win the hearts of customers. Barista's interpersonal communication is more persuasive. The hope is to grow customer loyalty. The purpose of this research is to determine the effect of barista interpersonal communication on Teras Senja Cafe customer satisfaction in increasing coffee sales and growing customer loyalty. The research uses interpersonal communication theory which has dimensions (Openness, Empathy, Supportive Attitude, Positive Attitude, and Equality). This type of research uses a quantitative approach with explanatory methods. The population consists of all the unknown number of Kopi Teras Senja customers, so a purposive sampling technique using the lemeshow formula was used to obtain 384 respondents with an error margin of 5% to represent Kopi Teras Senja customers. The research results show a significant influence between barista interpersonal communication on Teras Senja Cafe customer satisfaction with a value of 21.6%, while the remaining 78.4% can be influenced by variables outside of the research variables.